Switching from enoxaparin to dabigatran etexilate: pharmacokinetics, pharmacodynamics, and safety profile - Clemens, Andreas (Springer-Verlag, 2012)
PURPOSE: Dabigatran etexilate is an oral, reversible, direct thrombin inhibitor licensed for the prevention of venous thromboembolism and stroke prevention in patients with atrial fibrillation. The aim of this study was to investigate whether, and to what extent, a switch from enoxparin to dabigatran etexilate affects the pharmacokinetic (PK) and pharmacodynamic (PD) parameters and safety profile of dabigatran. METHODS: Enoxaparin 40 mg was administered subcutaneously once daily for 3 days followed by a single dose of dabigatran etexilate 220 mg (test treatment) on day 4 in an open-label, two-way cross-over trial in healthy volunteers. Dabigatran plasma levels were measured using a validated high-performance liquid chromatography tandem mass spectrometry method. Anticoagulant activity was measured using a number of clotting tests, including prothrombinase-induced clotting time (PiCT), activated partial thromboplastin time (aPTT), ecarin clotting time (ECT), and diluted thrombin time (dTT). RESULTS: PK, PD, and safety data were available for 23 subjects for each treatment. The adjusted geometric mean test/reference ratio of area under the concentration–time curve for total dabigatran was 84% (90% confidence interval 67.2–105.0%) and 86% (67.0–110.0%) for maximum plasma concentration. The PiCT test/reference ratio, which represents the activity of enoxaparin and dabigatran, was elevated by approximately 15% for peak maximum effect ratio to baseline and total area under the effect curve (AUEC(0-48)) activity, suggesting that some anticoagulant activity of enoxaparin was still present. Enoxaparin pre-treatment increased the AUEC(0–48) of activated partial thromboplastin time by approximately 14%. All other dabigatran-related PD markers were unaffected. Tolerability was good, with only mild and reversible adverse events during the treatment. CONCLUSION: Prior administration of enoxaparin did not meaningfully affect the PK or PD properties of dabigatran, and the switch from enoxaparin to dabigatran etexilate was well tolerated among the study subjects. These data support the safety of switching patients from enoxaparin to dabigatran etexilate.